Journal of Asset Management - diBartolomeo, Dan.; de Jong, Marielle; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan.)
The Journal of Asset Management covers: new investment strategies, methodologies and techniques new products and trading developments important regulatory and legal developments emerging trends in asset management Under the guidance of its expert Editors and an eminent international Editorial Board, Journal of Asset Management has developed to provide an international forum for latest thinking, techniques and developments for the Fund Management Industry, from high-growth investment strategies to modelling and managing risk, from active management to index tracking. The Journal has established itself as a key bridge between applied academic research, commercial best practice and regulatory interests, globally. Each issue of Journal of Asset Management publishes detailed, authoritative briefings, analysis, research and reviews by leading experts in the field, to keep subscribers up to date with the latest developments and thinking in asset management. Journal of Asset Management covers: asset allocation hedge fund strategies risk definition and management index tracking performance measurement stock selection investment methodologies and techniques portfolio management and weighting product development and innovation active asset management style analysis strategies to match client profiles time horizons emerging markets alternative investments derivatives and hedging instruments pensions economics.
Keywords: Finance; Finance, general; Financial Services; Risk Management